Measurement of the satisfaction of the direct users of the Department Programs on the Athmosphere of the Service of Aconcagua Health - Meléndez, Fancy; Arteaga, Oscar; Hernández, Enrique (Revista Chilena de Salud Pública, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The objective of this study was to assess the satisfaction degree of direct users of Aconcagua Health Service ’s Department of Environmental Programs. For this purpose, a survey was applied to a representative sample of 307 attended users between the months of October 2002 and February 2003. The applied instrument was specially designed for this study. Accessibility, infrastructure, interpersonal relationships, technical quality and global satisfaction were the dimensions considered. Sex, age, educational level, kind of procedure, and attention office variables were also considered. The high percentage of satisfaction due the rendered attention (73.61%) and the treatment offered by the officers as the best evaluated variable ( over 90% in all the cases), were some of the .findings of this study. The low rating of the resolving capacity for the complaints, with only a 18.6% of conformity with the solution, was also outstanding. The association analysis allowed to conclude that clarity of information and time of carrying out application are the most influential variables to the global satisfaction evaluation. Others findings were that users who perform more complex procedures and complaints gave a lower qualification to carrying out time (p<0.05), both procedures were carried through be women (p<0.05), who have a lower educational level (p<0.05) and gave a worse evaluation to clarity of information (p<O.I).